The Financial Performance and Credit Risk Management of Islamic Banks - Alamro, Omar Raja (Journal of Management World, 2025)
This paper investigates the effect of credit risk management on the financial performance of Islamic banks in Jordan in the context of a sample of employees of five Islamic banks. The demographic data showed that the majority of the respondents were in the 31–40 years age group (39.2%) and male (66.7%) and bachelor’s degree holders (62.9%) Credit risk management (4.1) and capital adequacy (4.2). The mean score for all the dimensions was between 4 and 5 reflecting a higher position. The time to get a loan approved was rated mid-size (3.5) – indicating operational improvement potential. The findings revealed a substantial positive correlation between credit risk management variables and financial performance indicators, with ROA at 0.72 and ROE at 0.68. The resource for performing structural equation modeling (SEM) confirmed the positive relationship between credit risk management and financial performance, with fit indices CFI = 0.95 and RMSEA = 0.05 suggesting a good fit. The above findings highlighted the importance of effective credit risk management practices to improve Islamic banks’ financial performance and financial soundness. The study recommends improving their training programs, streamlining loan approval processes, increasing reliance on FinTech, ensuring compliance, aiming for diversification, strengthening customer relationship management, and carrying out regular risk assessments. Possible studies in the future are to investigate the impact of new financial technologies and the regulatory alterations impact on Islamic banks’ credit risk management practices worldwide.